ACCOUNTANT ROLES AND INTEGRATED REPORTING IN MALAYSIA LOCAL AUTHORITIES - Sharifah Robiah Tuan Hazam (International Journal of Accounting, Finance and Business, 2023)
Integrated reporting is an innovation to corporate reporting that provides a unique reporting method focusing on creating value. However, accountant support for the development of integrated reporting in an organisation is crucial owing to their knowledge in financial capital of the organisation’s core resource. To ensure that the local authorities produce quality integrated reporting, it might be necessary for accountants to understand the reporting in connection to their responsibilities. Thus, the accountant's experience, knowledge and skills in assessing the entire organisation's actions in wider fields of sustainability information need to be discovered. The purpose of this study is to discuss the roles of accountant and their relationship with integrated reporting in Malaysia's local authorities. The challenges in the financial and nonfinancial activities of integrated reporting are also discussed. The sample consisted of four accountants and three assistant accountants from seven different local authorities. The finding revealed 90% agreement on the relationship between roles of accountants and integrated reporting. In addition, challenges in financial and nonfinancial activities, such as reporting, auditing and accounting information systems, were recognised.